Research Paradigms in English Education: A Brief Overview - Khatri, Dipendra Kumar (Surkhet Journal, 2023)
The researcher's worldview for the particular investigation is the research paradigm. So the main objective of this paper is to examine various forms of research paradigms with the library study attempting to link with English education. The description is tried to make clear by linking with examples of selected an issue. For this, the paper starts by introducing a research paradigm as the looking glass to the world. So it is the lens of the researcher through which the study is completed. It was found that positivism is based on objective reality which is most appropriate in natural science and post-positivism is the modification (of positivism) as demands more interaction between the researcher and participants. On the other hand, interpretivism is to understand the issue from an insider's view and constructivism is aimed at social construction. Furthermore, criticalism is to improve the situation of the oppressed, and feminism is purposeful to empower females. Moreover, pragmatism is to generate context-based knowledge and post-modernism is to explore representational knowledge. In a sense, integralism is to integrate different paradigms within one single research. This paper also explores the components of the research where ontology is a study of reality, epistemology is the study of knowledge generation, and methodology is the process of doing the particular research. It implicitly reflects the axiology as the study of value systems. Overviewing the various shifts from traditional to relatively today's research, the specific issues are selected in connection to English education and suggested to link them contextually.